개방형 협업(open collaboration)방식의 비즈니스 모델 사례 분석 연구 - 백경화; Baek Kyoung Hwa; 하은아; Ha Eun A; 조재경; Cho Jae Kyung (기초조형학연구, 2017)
본 연구는 공동 가치 창출을 위한 새로운 혁신 방식 중 하나인 개방형 협업의 의미와 다양한 유형의 양상을 파악하고, 이를 바탕으로 개방형 협업의 구조와 어떠한 요소들이 유의미한 성과를 내는지 알아보는 것을 목적으로 한다. 연구 범위는 문헌과 선행연구, 글로벌 기업의 보고서를 참고하여 5가지 협업 유형 중 기업과 소비자의 참여 강도에 따라 오늘날 실질적 개방형 협업으로 볼 수 있는 3가지 협업 유형을 사례분석을 위한 연구 범위로 설정하였다. 연구 대상 선정은 구글 키워드 검색과 선행연구에서 빈번히 언급되거나, 성공 사례로 선정된 것을 참고하여 독창적인 비즈니스 모델을 가진 해외 기업 7개를 선정하였다. 분석을 위해 공유(협업) 방법과 결과물의 내용, 의사결정 방식, 참여자 유도방식 그리고 기업과 소비자 측면을 분석의 기준으로 하였으며, 자세한 내용은 3장에서 다루었다. 이를 통해 나타나는 특징을 정리하면 다음과 같다. 서비스 리디자인(service redesign)은 소비자의 의견과 아이디어를 적극적으로 수렴하여 제품과 서비스의 경험을 재설계하고 있으며, 특히 협업의 장벽이 낮아 다양한 정보 교류와 소비자들 중심의 사회적 네트워크를 형성하고 있었다. 뉴 프로덕트 코크리에이션(new product co-creation)은 제품 개발에 소비자가 능동적으로 참여하여 기업과 공동 작업하고 있으며, 제품 개발 전 과정에서 활발히 의견을 공유하고 있었다. 커뮤니티 프로덕트 디자인(community product design)은 소비자가 기업의 제품 개발 및 생산 활동 전반에 주체자로서 비즈니스를 주도하고 있었으며, 아이디어를 제품으로 창작하는 참여형 소비자의 모습을 보였다. The purpose of this study is to investigate the meaning and different types of aspects of open collaboration which is one of the new innovation system for creating shared value, and to investi gate which structure and elements of open collaboration make significant outcome. This study set 3 collaboration types that can be considered as the real open collaboration today for case analysis according to the intensity of participation of business and consumers among 5 types of collaboration types by referring to literature, precedent studies, and reports of global enterprises. For selection of research subjects, this study selected 7 overseas companies with a creative business model who have been frequently mentioned on Google keyword search and precedent studies or selected as a successful case. A sharing(collaboration) method, contents of outcome, decision-making method, guidance system of participants, and enterprise and consumer aspects were set as the standard of analysis, and details are covered in Chapter 3. Characteristics that appeared through this process are as follows. Service redesign is redesigning products and experiences of consumers by actively collecting opinions and ideas of consumers, and specially, it was forming a variety of information exchange and consumer oriented social network because the barrier of collaboration was low. For new product co-creation, consumers participated actively in product development and collaborated with businesses, and were actively sharing opinions during the whole process of product development. Consumers were taking the lead in businesses as a main agent in product development and production activity for community product design, and have been prosumer who create ideas into products.